The (im)possibility of filming Ibsen - Chen, Melvin (Nordlit, 2015)
This article begins by taking the paucity of good filmed versions of Ibsen as an empirical fact or a given, as it were. It then introduces the Shakespeare premise, which it proceeds to adopt as valid. This opens up the possible conclusion that great film adaptations might arise from great dramatic texts, a possibility strengthened by my second premise that cinema and theatre constitute sister arts, particularly in the Bazinian realm of mixed cinema. At the same time, the Shakespeare premise allows me to suspend the immediate conclusion that it is impossible to make great filmed versions of Ibsen, a suspension of judgment reflected in the use of brackets in the title of my article. After dispensing with Panofsky’s thesis of strict antithesis as a false premise, I adopt a Bloomian framework to discuss how plays by Ibsen may be adapted so as to fulfil the Shakespeare premise. I consider how aesthetic principles may be developed so as to aid the potential film-maker who is likewise driven by the Shakespeare premise and the concomitant hidden potential in Ibsen, whose dramatic texts share the natural priority and canonical prestige of Shakespeare’s texts. My final conclusion remains open-ended but positive: the day in which filmed versions of Ibsen might fulfil the Shakespeare premise with ease remains on the horizon, although my discussion will – I hope – have gone some way in helping bring that film-in-the-making into fruition.